Vocabulary knowledge and vocabulary learning strategies among English majors in a Saudi Arabia University - Alharbi, Jamilah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study seeks to investigate the relationship between vocabulary knowledge and vocabulary learning strategies of first-year students at the Department of English Language and Literature at the University of Majmaah. This study also examines whether there are significant gender differences in terms of vocabulary knowledge and the strategies preferred in their vocabulary acquisition. The researcher conducted the study on 65 students from Majmaah University who were made up of first-year English major students. The instruments used in the study were the Vocabulary Levels Test (VLT) by Nation (2001) and Schmitt et al. (2001), the Lexical Frequency Profile (LFP) by Laufer and Nation (1995), and the Vocabulary Learning Strategies questionnaire (VLSs) by Schmitt (1997). The VLT and LFP were used to assess the participants' receptive and productive vocabulary knowledge respectively. The VLSs questionnaire was used to identify the strategies preferred by these English major students in learning new vocabulary items. Among others, the findings of this study reveal that the productive vocabulary knowledge of male students is significantly lower at the 3,000 word level compared to the 1,000 word level. Female learners performed better compared to males in the productive VLT. Findings of this study also reveal that the participants preferred social strategies in learning new words. Additionally, the study examined the correlations between every vocabulary level (1,000 words, 2,000 words, 3,000 words, 5,000 words, 10,000 words and Academic word level (AWL) and the VLSs used (social, meta-cognitive, cognitive, determinant and memory). This study serves as a guideline for English teachers to adopt appropriate and effective strategies in the teaching of vocabulary to Saudi students in tertiary institutions. It also fills the gap of knowledge regarding gender differences in acquiring receptive and productive vocabulary among Saudi EFL learners.